Firm Resources as Moderators of the Relationship Between Market Growth and Strategic Alliances in Semiconductor Start-UPS - Park, Seung Ho; Chen, Roger; Gallagher, Scott (Academy of Management Journal, 2002)
This article examines interactions between internal and external drivers of alliance formation. We argue that firms' use of alliances as a mechanism to adapt to market uncertainties is contingent on internal resource conditions. The results indicate that, in volatile markets, resource-rich firms access external resources through alliances whereas resource-poor firms are less likely to do so. However, in relatively stable markets, this relationship reverses, and resource-poor firms become more active in alliance formation.